Dari Tauhid Ritualistik ke Tauhid Emansipatoris: Rekonstruksi Teologi Islam Transformatif Berbasis Tazkiyatun Nafs dalam mengatasi Disjungsi Spiritualitas dan Realitas Sosial - Luna Fairuzzahiyah; Maharani Duhita Renata Sani; Hilyah Bariroh; Zajilatur Rohmah; Ali Hasan Siswanto (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
This article departs from an academic crisis characterized by a disjunction between normative-ritualistic Islamic theology and a social reality marked by inequality, conflict, and pragmatism. Although theology possesses transformative potential, contemporary religious practices tend to remain individualistic and lack the capacity to effectively respond to social, political, and economic challenges. The research gap lies in the limited integration of theology, Sufism—particularly tazkiyatun nafs—and social praxis within a systematic and emancipatory framework. This study employs a theoretical approach of transformative tazkiyatun nafs grounded in emancipatory tawhid, positioning self-purification as the foundation of social change. The research method is qualitative-conceptual, utilizing library research with philosophical, theological, and hermeneutical analysis. The main argument asserts that the reconstruction of Islamic theology must shift from ritualistic tawhid toward emancipatory tawhid that integrates spiritual, ethical, and practical dimensions. The findings indicate that tazkiyatun nafs can be transformed from an individual practice into a social paradigm that shapes collective consciousness toward justice. The scholarly contribution of this study lies in the formulation of an integrative model of theology–Sufism–social transformation as a new paradigm in contemporary Islamic studies.